THE EFFECT OF CHANGES IN THE MAIN CHARACTERS PERSONALITY TOWARDS SOCIAL SETTING IN LOIS LOWRYS THE GIVER - Khairulsyah S; Ni Made Widisanti S; Tetty Yukesti (Journal Albion : Journal of English Literature, Language, and Culture, 2021)
The title of this research is "The Effect of Changes in the Main Characters Personality towards Social Setting in the Novel The Giver by Lois Lowry'". The aim of this research is to point out that personality changes can have an impact on  environment. Analysis descriptive method and library research are the method and technique used in conducting this research. The result of this study show that Jonas  has experienced change after he receives training as The Receiver and feels that something has gone wrong with the place called The Community. Memories of the beauty of the past makes him realize that the ritual called releaseâ€ was actually an assassination. In the end, these influences made Jonas leave The Community to save his environment and to return  it back to normal.Keywords : social background; psychology.